2019
DOI: 10.2460/javma.254.1.104
|View full text |Cite
|
Sign up to set email alerts
|

Suicide among veterinarians in the United States from 1979 through 2015

Abstract: OBJECTIVE To assess proportionate mortality ratios (PMRs) for suicide among male and female US veterinarians from 1979 through 2015. DESIGN PMR study. SAMPLE Death records for 11,620 veterinarians. PROCEDURES Information for veterinarians who died during 1979 through 2015 was obtained from AVMA obituary and life insurance databases and submitted to a centralized database of US death records to obtain underlying causes of death. Decedent data that met records-matching criteria were imported into a softwar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
101
0
8

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(111 citation statements)
references
References 48 publications
2
101
0
8
Order By: Relevance
“…‘Letting the Cat Out of the Bag’ fails to acknowledge one of the most serious public health risks associated with current urban stray cat management policies in Australia: the impact on the mental health of shelter staff tasked with euthanizing healthy animals [4,5]. Results of a recently published US study reveal a suicide rate among veterinarians that is up to 3.5 times higher than the national suicide rate, with ‘euthanasia procedures’ identified as a likely contributing factor [22]. Staff forced to euthanize healthy cats and kittens often suffer from debilitating ‘moral stress’ [23] and are at high risk of depression and perpetrator-associated traumatic stress.…”
Section: Alleged Public Health Risksmentioning
confidence: 99%
“…‘Letting the Cat Out of the Bag’ fails to acknowledge one of the most serious public health risks associated with current urban stray cat management policies in Australia: the impact on the mental health of shelter staff tasked with euthanizing healthy animals [4,5]. Results of a recently published US study reveal a suicide rate among veterinarians that is up to 3.5 times higher than the national suicide rate, with ‘euthanasia procedures’ identified as a likely contributing factor [22]. Staff forced to euthanize healthy cats and kittens often suffer from debilitating ‘moral stress’ [23] and are at high risk of depression and perpetrator-associated traumatic stress.…”
Section: Alleged Public Health Risksmentioning
confidence: 99%
“…Veterinary professionals' high rates of stress, burnout, and emotional exhaustion (31) are especially alarming given the fact that male veterinarians' suicide rates are 2.1 times as high and female veterinarians are 3.5 times as high as the general U.S. population (32). They are also more likely to die from suicide than other health care professionals (33).…”
Section: Introductionmentioning
confidence: 99%
“…The full quotes are (i): 'Additionally, research has indicated specific characteristics of the profession likely contribute to a greater than expected number of deaths from suicide among veterinarians, including long work hours, work overload, practice management responsibilities, client expectations and complaints, euthanasia procedures (our italics), and poor work-life balance.' ( [63], p. 109); and (ii) 'Other factors likely include financial debt and knowledge and acceptance of euthanasia procedures (our italics) as well as access to potentially lethal pharmaceutical products. Additionally, veterinarians are trained to view euthanasia as an acceptable method to relieve suffering in animals, which can affect the way veterinarians view human life, including a reduced fear about death, especially among those experiencing suicidal ideation.'…”
Section: Tnr Will Reduce Problems Associated With Urban Cat Populationsmentioning
confidence: 99%
“…Additionally, veterinarians are trained to view euthanasia as an acceptable method to relieve suffering in animals, which can affect the way veterinarians view human life, including a reduced fear about death, especially among those experiencing suicidal ideation.' ( [63], p. 110) In Australia specifically, Jones-Fairnie et al [64] raised concern about suicide rates in veterinarians. A more detailed follow-up study noted: ' ... disturbances in psychological well-being are a major problem in the veterinary profession.…”
Section: Tnr Will Reduce Problems Associated With Urban Cat Populationsmentioning
confidence: 99%